Effect of helium plasma gas flow rate on the properties of WC-12 wt.%Co coatings sprayed by atmospheric plasma - Mrdak, Mihailo R. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The cermet coatings of WC-12wt.%Co are extensively used to improve the wear resistance of a wide range of technical components. This paper analyses the influence of the plasma gas flow of helium on the microstructure and mechanical properties of WC-12wt.%Co coatings deposited by plasma spraying at atmospheric pressure (APS). In order to obtain homogeneous and denser coatings, three different flows of He ( 8 l/min., 16 l/min. and 32 l/min) were used in the research. With the application of He, coatings achieved higher values of hardness due to less degradation of the primary WC carbides. The main goal was to deposit dense and homogeneous layers of WC-12wt.%Co coatings with improved wear resistance for different applications. The test results of the microstructure of the layers were evaluated under a light microscope. The analysis of the microstructure and the mechanical properties of the deposited layers was made in accordance with the standard of Pratt-Whitney. The morphology of the powder particles and the microstructure of the best coating was examined on the SEM (scanning electron microscope). The evaluation of the mechanical properties of the layers was done by applying the HV0.3 method for microhardness testing and by applying tensile testing to test the bond strength. The research has shown that the flow of He plasma gas significantly affects the microstructure, the mechanical properties and the structure of WC-12 wt.%Co coatings.